Kajian Mengenai Potensi dan Prospek Pengembangan Agrowisata di Kecamatan Karangreja Kabupaten Purbalingga - Supadi Supadi; Rahab Rahab; Rusmusi Rusmusi (Ilmu Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Unsoed, 2011)
ABSTRACT Harmony between agriculture and tourism in the form of agro-tourism development can be as an alternative to economically empowering village community. In efforts to develop and maximize the various potentials and local resources necessary agro-tourism development that emphasizes local community participation. Development of agro-tourism is expected to inhibit the rate of urbanization as agrotourism can create economic activity, employment and additional income to local communities. The specific objectives of this research are: 1) find and recognize the potential of agriculture, plantations, livestock, and natural potential to be developed as a tourist attraction. , 2) explore a variety of resources (natural, social, cultural) and the other bearing capacity to support tourism development in order to empower rural communities; 3) to identify resources to support rural communities in agro-tourism development; 4) identify strengths (Strengths), opportunities (Opportunities) , weakness (Weaknesses) and threats (Threats) of the potential and resources of the village. The research location is in Sub-Karangreja Purbalingga. Site selection is done by the consideration that the District has the potential Karangreja and agricultural resources that can be directed to the development of agrotourism. Technic of samples will be used in this study was purposive sampling with snowball method. Data collection techniques will be used in this study include: observation, interviews (in-dept interview), seminars and focus group discussion (focus group Discusion). Data are analyzed with techniques interakatif model analysis (Miles and Hubermann, 1992) which covers components: (1) data collection, (2) data reduction, (3) presentation of data (4) conclusion (verification). The data also are reviewed with a SWOT analysis to identify strengths, weaknesses, opportunities and threats of rural community economic development through agro-tourism development for models that have been formulated in accordance with the characteristics of the components developed. The findings of research will be the basis for future research. Keyword: agro-tourism, community, rural, development